2007
DOI: 10.1007/s10461-007-9258-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Drug Use, and Perceived Social Support Among HIV Positive Patients

Abstract: We investigated the relationships among gender, drug use, and perceived social support in 176 HIV positive patients recruited with their informal caregivers in HIV clinics. Perceived caregiver support, emotional support, tangible support, and conflict were assessed. Current drug use was defined as heroin and/or cocaine use within 6 months prior to baseline. Gender was not significantly associated with any of the four outcomes. Current drug users reported significantly higher conflict in social relationships th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…In particular, Peterson et al ( 2011 ) observed that social support may enhance various stress coping strategies, thus improving well-being among PLWH. Specifically, perceived support led to a lower level of substance use among participants, which corresponds with the findings of Rothman et al ( 2008 ), who observed that drug use were related to dissatisfaction in perceived social support among PLWH.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, Peterson et al ( 2011 ) observed that social support may enhance various stress coping strategies, thus improving well-being among PLWH. Specifically, perceived support led to a lower level of substance use among participants, which corresponds with the findings of Rothman et al ( 2008 ), who observed that drug use were related to dissatisfaction in perceived social support among PLWH.…”
Section: Discussionsupporting
confidence: 88%
“…Our preliminary findings are consistent with other studies 26,29 and those which show that the availability of social support systems increases the likelihood of practicing protective health behaviors including reduced or nondrug use 2,42 . For example, greater social support predicted better mental health status and less heroin and cocaine use among individuals with co‐occurring substance use and psychiatric disorders 42 .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, high levels of social support were shown to be inversely related to psychological distress among college students: its effects on distress were mediated by attachment 28 . Among adolescents, the relationship between stressful life events and drug use is moderated by the level of social support they receive from family and friends 29 . Hence, it is not surprising that both high levels of social support and good quality of attachment relationships are inversely associated with the lifetime use of illicit substances 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of positive sources of social support on emotional well-being and risk-avoidant and medicationtaking behaviors among those with HIV are clear. [42][43][44][45][46] More research is needed to investigate ways in which other family members and friends play supportive roles, as well as the way in which health care professionals can facilitate the development of supportive networks for those with HIV in order to improve health care experiences and treatment outcomes.…”
mentioning
confidence: 99%